Liquidity Risk Management in Islamic Banks in The Digital Era - Bunga Andini; Syafnur Muhammad Rizki; Wahyu Febri Ramadhan Sudirman (Global Sustainability Research Institute, 2025)
This study discusses liquidity risk management in Islamic banks in the digital era, focusing on strategies implemented to maintain financial stability amidst technological developments. Digital transformation in the banking industry brings opportunities and challenges, including increasing service efficiency and more complex liquidity risks due to changes in transaction patterns and customer preferences. This study uses a quantitative approach with secondary data analysis from Islamic bank financial reports and relevant liquidity indicators. The results of the study indicate that the application of financial technology (fintech) and digital-based risk management strategies can improve the liquidity resilience of Islamic banks. In addition, the optimization of Islamic financial instruments, such as Sukuk and Sharia-based interbank markets, is a key factor in maintaining liquidity balance. Thus, this study provides insight for Islamic banking regulators and practitioners in designing policies that are adaptive to digital changes to strengthen the resilience of the Islamic banking sector.